S.Typhi derived OmpC peptide conjugated with Vi-polysaccharide evokes better immune response than free Vi-polysaccharide in mice. (November 2019) - Haque, Shabirul; Sengupta, Sanjukta; Gupta, Dinesh; Bhan, Maharaj Kishan; Kumar, Ramesh; Khan, Azhar; Jailkhani, Bansilal
Abstract: Salmonella typhi is a causative organism for typhoid fever. Free Vi capsular polysaccharide (Vi) is licensed for use as vaccine for typhoid fever in individuals 2 years of age and older, which has limited memory response. There is dire need of protein or peptide as conjugate partner with Vi polysaccharide to improve shortcomings of Vi vaccine. Prediction of immunogenic peptide was deduced by program T sites. Carbodiimide mediated conjugation of Vi polysaccharide with OmpCp was performed utilizing ADH as linker. Immune response of Vi-conjugates along with control group was tested in mice. Ig and IgG antibodies against Vi polysaccharide was measured by ELISA. Two immunodominant regions (loop number 3a and 7) with high content of T-cell epitopes from OmpC was selected and synthesized. Vi poly/OmpCp ratios in Vi-conjugates were ~0.43–0.65. Vi polysaccharide alone elicited very low levels of Vi antibody without any booster effect. Vi-conjugate evoked 20-fold higher immune response compared to free Vi. Further, adequate levels of IgG antibodies were induced only by the Vi-conjugate suggesting that T-helper cells had been induced. Our data suggest that selected short peptide (OmpCp)as a carrier with Vi polysaccharide is assumed to be a promising molecule for candidate vaccine for typhoid fever.